Slang Words Used in The Fast and The Furious: Tokyo Drift Movie - Ni Putu Terri Wirantari; I Nyoman Tri Ediwan; Ni Ketut Sri Rahayuni (CV. Ulil Albab Corp, 2022)
Slang Terms Used in The Fast and the Furious: Tokyo Drift Movie is a study.The purpose of the study is to recognize and categorize the various slang terms used by characters in the film to express their meanings. The Slang Words Used in The Fast and the Furious: Tokyo Drift Movie movie served as the source for the data for this study. The data was collected using a documentation approach, and the varieties of slang and their meanings were described using a qualitative method. There are seven types of meanings, they are conceptual meaning, connotative meaning, social meaning, affective meaning, collective meaning, reflective meaning and thematic meaning.